An Adaptive Automatic Braking System for Enhanced Road Safety : English - Pratama, Wildan; Cahya Happyanto, Dedid; Wijayanto, Ardik; Alrijadjis, Alrijadjis; Madyono, Madyono (Universitas Muhammadiyah Surakarta, 2025)
The fuzzy logic-based automatic braking system was developed to improve driving safety by reducing reliance on the driver's attention. The system integrates a LiDAR sensor for distance, a magnetic speed sensor for speed, and an ESP32 microcontroller as the main control. The advantage of this system lies in its ability to process data from various parameters adaptively and quickly using the rules of fuzzy logic. Communication between modules is supported by the CANBUS protocol to ensure fast and accurate data exchange. Tests show that the LiDAR proximity sensor has high accuracy with an average error of less than 1%. The speed sensor shows a consistent relationship between the frequency of the inverter and the speed of the car, with an average error of 7.1% on the deceleration. The fuzzy system successfully replicates MATLAB output with relatively few errors, and a more stable Duty Cycle setting than without fuzzy. This proves that the system is adaptive and responsive in a wide range of operational conditions.